*La investigación-acción mejora la planeación de clases en lengua extranjera - Quintero C., Josefina; Zuluaga C., Carmen; López P., Margarita (Íkala, Revista de Lenguaje y Cultura, 2003)
This article is derived from an action research project developed at the University of Caldas in Manizales-Colombia with a group of teacher-trainees who are carrying out their teaching practicum at State Schools. It describes the most common problems and the strengths that the practicum advisors have observed at the moment of revising the trainees’ lesson plans. It includes some examples taken from the trainees journals with the corresponding advisors suggestions. The researchers describe the intervention points to improve the advising actions that could allow the trainees to reflect on their planning weaknesses. Advisors, as facilitators of that process, feel that there is something to contribute with the pedagogical knowledge about classroom research. Received: 27-01-03 / Accepted: 14-07-03. How to reference this article: Quintero C., J., Zuluaga C., J. & López P., M. (2003). La investigación-acción mejora la planeación de clases en lengua extranjera. Íkala. 8(1), pp. 39 – 56